Navigating the sedation challenge in frail older patients undergoing endoscopic retrograde cholangiopancreatography: a narrative review - Koji Takahashi; Nana Yamada; Terunao Iwanaga; Takafumi Sakuma; Hidehiro Kamezaki (Discover Medicine, 2026)
Abstract The global increase in life expectancy has resulted in a higher volume of endoscopic retrograde cholangiopancreatography (ERCP) procedures among frail older patients. Frailty, a multidimensional syndrome characterized by decreased physiological reserve, presents significant risks for sedation-related adverse events. Current sedation practices frequently rely on data derived from younger cohorts, often failing to account for the distinct pharmacokinetic and pharmacodynamic profiles associated with frailty. This review evaluates the multifaceted challenges of sedating this vulnerable population. We analyze the roles of sarcopenia, hypoalbuminemia, and neuroinflammation in predicting procedural outcomes. We compare different delivery models, including endoscopist-directed sedation (EDS), and anesthesia-assisted sedation (AAS), while aligning with major clinical guidelines on sedation depth. Furthermore, we evaluate recent pharmacological developments, such as remimazolam—a reversible ultra-short-acting benzodiazepine receptor agonist whose designation as a universal first-line sedative in elective settings awaits prospective validation in severely frail patients, and whose supporting efficacy–safety evidence rests substantially on a single non-frail randomized trial (see Sect. 5.2), and whose preference over propofol in emergency ERCP complicated by hemodynamic instability, while clinically reasoned, remains based largely on extrapolated evidence from non-emergency, non-frail cohorts—alongside advanced monitoring technologies. A critical finding of this review is that the majority of existing ERCP outcome studies in older patients were designed to assess technical feasibility rather than sedation safety: sedation-specific adverse events were not systematically reported as primary or secondary endpoints in most identified studies. This evidence gap itself represents a central finding of our narrative synthesis, underscoring the urgent need for prospective trials specifically designed to evaluate sedation-related outcomes in frail older patients undergoing ERCP. We propose a structured clinical framework for precision sedation that integrates validated frailty assessments, shared decision-making, and a proposed post-procedural recovery protocol. Importantly, this framework represents a proposed, hypothesis-generating pathway derived from extrapolated evidence and expert consensus, and has not been prospectively validated in ERCP-specific frail populations. This approach aims to preserve the functional and cognitive independence of frail older patients, moving beyond technical procedural success to prioritize patient-centered outcomes.